Cultural disposition influences in workgroups: A motivational systems theory of group involvement perspective - HINSZ, Verlin B. (Institutional Knowledge at Singapore Management University, 2019)
Modern organizations often involve workgroup members who have different cultural heritage. This article provides an examination of how different cultural dimensions (e.g., uncertainty avoidance, individualism–collectivism) influence the ways that workgroups and their members respond to situations that involve threats and rewards. The threats and rewards activate distinct response patterns that are associated with a motivational systems theory of group involvement. Based on this theoretical foundation, a cultural dispositions approach is applied to reveal how culture could impact the ways group members respond (cognitively, affectively, motivationally) to situations that involve varying degrees of threats or rewards. This focus on cultural dispositions locates this article in the larger theoretical context of persons within situations that account for complexities of threat and reward cues as well as groups, organizations, and cultures. Consequently, this article has broad implications to the scientific and applied science communities interested in multicultural workgroups.